Diagnostic value of ultrasound elastography in polycystic ovary syndrome: a systematic review and meta-analysis - Zhongtan Ruan; Zhen Yu; Qianyu Qin; Ying Tang (Gynecological Endocrinology)
Objective The main purpose of this systematic review and meta-analysis was to investigate the diagnostic value of ultrasound elastography in the evaluation of polycystic ovary syndrome (PCOS).Methods A comprehensive and methodical investigation was carried out in the databases of PubMed, EMBASE, Cochrane, Scopus, Web of Science, and China National Knowledge Infrastructure, covering the entire duration of these databases until October 18, 2023. The primary purpose of this research was to evaluate and contrast ovarian tissue elasticity in people with and without PCOS. The elasticity of ovarian tissue was quantified using standardized mean difference (SMD).Results A total of eight studies were ultimately selected for systematic evaluation and meta-analysis. Five studies used shear wave elastography (SWE) as a diagnostic tool, and it was discovered that women with PCOS had higher levels of ovarian shear wave elasticity than their healthy counterparts. The SMD was determined to be 1.86 kilopascal (95% CI: 1.27 to 2.44). Three studies were conducted using strain elastography (SE) to compare the ovarian strain ratio of patients with PCOS to that of a healthy control group. The SMD for the PCOS group was 2.07 (95% CI: 1.79 to 2.34), which indicated that the ovarian strain ratio was significantly higher in that group.Conclusion This systematic review and meta-analysis found that women with PCOS had stiffer ovarian tissue than women without the disorder. Ultrasound elastography may provide clinicians with value beyond 2D ultrasound in the diagnosis of PCOS.